Two-phase flow characteristics of different charging structure in ignition and flame-spreading. Issue 4 (7th June 2021) - Shenshen, Cheng; Ruyi, Tao; Shao, Xue; Xinggan, Lu; Hao, Wang
Abstract : To study the influence of flame-spreading behaviour in the ignition process of different charging structures in high-density charge chambers, a visualisation device was designed, and the ignition process of the two charging structures was researched. The flame-spreading process was observed by a high-speed digital camera system and the pressure data was recorded by a data acquisition instrument. According to the experiment, a two-dimensional axisymmetric internal ballistic two-phase flow model was established to simulate the flow process of gas in particle bed based on the Weighted Essentially Non-Oscillatory (WENO) Scheme. The results show that the flow field and flame-spreading status in different charging structures are different. In the full charging structure, the development of the flow field is regular, the flow field in the entire chamber has less fluctuation areas, and velocity vortices only generate during the development of the flow field and when it reaches the wall. However, in the partially charging structure with free space, there are many pressure fluctuation areas in the flow field in the chamber, and the flow field development is also uneven. Pulsating propagation occurs at the interface between particles and free space, which has a great influence on the whole combustion and ignition process. The research results reveal the characteristics of two-phase flow in different charging structures and provide a reference for the actual charging process.